Authoritarian populism in the US: context and continuity in a post-truth era - Box, Richard C. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
An enduring theme in US politics is tension between people on the right who favour limited government that serves individual and elite interests and people on the left who prefer active government with emphasis on a broader public interest. Recently, the political landscape has shifted from the dominant ideology of neoliberalism toward a far-right authoritarian populism with parallels to mid-20th century fascism.
Keywords: authoritarian populism; cultural context; fascism; post-truth; elite; white nationalism